A Qualitative Study on the Supportive Care Needs Preferences of Older Colorectal Cancer Patients: Insights from Patient Experiences - Li X; Wu L; Zhang M; Yao L; Zhou N; Li Y; Song X; Zhou H; Song A; Zhou J (Patient Preference and Adherence)
Xiaowan Li,1,* Luqing Wu,2,* Mengqi Zhang,3,* Liqun Yao,4,* Na Zhou,1 You Li,5 Xinying Song,6 Huiyue Zhou,1 Anni Song,1 Jiao Zhou1 1Nursing Department, Ninth People’s Hospital of Zhengzhou, Zhengzhou, Henan Province, 450053, People’s Republic of China; 2Department of Critical Care Medicine, The First Affiliated Hospital of Xiamen University, Xiamen, Fujian Province, 361000, People’s Republic of China; 3Breast Surgery Department 3, The Third Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province, 450000, People’s Republic of China; 4Weifang Center for Disease and Prevention, Weifang, Shandong Province, 261061, People’s Republic of China; 5General Surgery Department, Ninth People’s Hospital of Zhengzhou, Zhengzhou, Henan Province, 450053, People’s Republic of China; 6School of Nursing and Health, Zhengzhou University, Zhengzhou, Henan Province, 450001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huiyue Zhou, Ninth People’s Hospital of Zhengzhou, Zhengzhou, Henan Province, 450053, People’s Republic of China, Email ZH_Y221220@163.com Xinying Song, School of Nursing and Health, Zhengzhou University, Zhengzhou, Henan Province, 450001, People’s Republic of China, Email songxinying2021@163.comPurpose: This study employs a qualitative research methodology to explore the genuine feelings of older patients with colorectal cancer (OPCRC) regarding their Supportive Care Needs (SCNs), to understand their specific care requirements and to inform the clinical implementation of targeted intervention programs.Methods: Qualitative research was conducted from November 2024 to January 2025 in Zhengzhou, China. Data were collected through in-depth, semi-structured interviews with OPCRC. Thematic analysis was employed to identify key themes from the interview transcripts.Results: A total of 25 participants were recruited, comprising 18 males and 7 females. Thematic analysis revealed four themes and 13 sub-themes: 1) disease management needs, 2) information acquisition needs, 3) emotional support needs, and 4) practical needs.Conclusion: It is essential to prioritize the care needs of OPCRC by enhancing symptomatic management and providing comprehensive information support. Additionally, addressing their emotional well-being is crucial, and effective social assistance should be offered to facilitate their reintegration into society.Keywords: older people, care, colorectal cancer, qualitative research